Segregación : fundamento de la fraternidad (2013)
ABSTRACT: This article develops the thesis that, both the works of Freud and Lacan, make it possible to approach to the concepts of segregation, exclusion and conflict, by posing a way beyond cultural ideals and, in that sense, a difference between the social link, based on love and the spirit of solidarity, and the phenomena that encourage segregation. Psychoanalysis can show that the foundation of any segregation is fraternity, which brings to the fore current issues of contemporary cultural logics.